2009
DOI: 10.1055/s-0029-1243121
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Flavones from the Roots ofScutellaria baicalensiswith the Benzodiazepine Site

Abstract: A radioreceptor binding assay was used to guide the isolation of four chemical constituents in the organic solvent extracts of Scutellaria baicalensis Georgi capable of binding to the benzodiazepine site (BZD-S) of the GABAA receptor: wogonin (Ki = 2.03 +/- 0.24 microM), baicalin (Ki = 77.10 +/- 4.79 microM), baicalein (Ki = 5.69 +/- 0.95 microM), and scutellarein (Ki = 12.00 +/- 1.27 microM). All four compounds contain the flavonoid phenylbenzopyrone nucleus. Based on BZD-S binding, the order of affinity amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 5 publications
(5 reference statements)
0
30
0
Order By: Relevance
“…They exert a wide-range of health-promoting effects including antioxidative, anti-inflammatory, cardioprotective, anticarcinogenic, antidiabetic and neuroprotective activities [204][205][206]. Like many neuroactive drugs, they achieve their effects, at least in part, by modulating GABAA receptors [207,208]. Radioligand binding studies indicated that flavonoids exert a selective affinity for the benzodiazepine binding site at GABAA receptor complex, mostly acting as partial agonists [209].…”
Section: Interactions Of Flavonoids With Gabaa Receptormentioning
confidence: 99%
“…They exert a wide-range of health-promoting effects including antioxidative, anti-inflammatory, cardioprotective, anticarcinogenic, antidiabetic and neuroprotective activities [204][205][206]. Like many neuroactive drugs, they achieve their effects, at least in part, by modulating GABAA receptors [207,208]. Radioligand binding studies indicated that flavonoids exert a selective affinity for the benzodiazepine binding site at GABAA receptor complex, mostly acting as partial agonists [209].…”
Section: Interactions Of Flavonoids With Gabaa Receptormentioning
confidence: 99%
“…For example, Targeted Modulation of Neural Circuits Implicated in Anxiolysis chrysin, one of the first flavonoids shown to interact with the BZD binding site, initiated the search for natural anxiolytics among traditional medicinal herbs (Medina et al, 1989(Medina et al, , 1990(Medina et al, , 1997Wolfman et al, 1994Wolfman et al, , 1996. A number of other naturally occurring flavonoids and their derivatives, such as K36 (5,7,29-trihydroxy-6,8-dimethoxyflavone) (Huen et al, 2003), hispidulin (Kavvadias et al, 2004), wogonin (Hui et al, 2000(Hui et al, , 2002, and related compounds (Nielsen et al, 1988;Häberlein et al, 1994;Wolfman et al, 1996;Goutman et al, 2003), are allosteric modulators at GABA A Rs. In a mouse study, wogonin (7.5-30 mg/kg p.o.)…”
Section: Benzodiazepines and Related Modulatorsmentioning
confidence: 99%
“…A study (Liao et al, 1998), indicated oroxylin A, baicalein and wogonin, which are flavonoids found in S. lateriflora, had weak affinities for the benzodiazepine site of GABA A receptors in mouse cerebral cortex in vitro. In another study Hui et al (2000) tested the capacity of baicalin, baicalein, scutellarein and wogonin to bind to the benzodiazepine site of the GABA A receptor in homogenised rat brain. Affinity to the benzodiazepine site for scutellarein was moderate and weak for baicalin.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Contrary to results of the earlier study (Liao et al, 1998) the binding affinities of wogonin and baicalein were strong. The authors suggested the discrepancy may be due to differences in species and assay models used (Hui et al, 2000).…”
Section: In Vitro Studiesmentioning
confidence: 99%